Human erythrocyte membrane fluidity and insulin binding are independent of dietary trans fatty acids - Berlin, Elliott; Bhathena, Sam J.; Judd, Joseph T.; Clevidence, Beverly A.; Peters, Renee C. (The Journal of nutritional biochemistry, 1994)
Substitution of selected saturated fatty acids of the diet of 29 men and 29 women with cis or trans monounsaturated fatty acids did not affect erythrocyte membrane fluidity, insulin binding, and the membrane cholesterol and phospholipid concentrations. Subjects were fed four different controlled diets with a total fatty acid content of 39 to 40 energy percent for four 6-week periods in a Latin square design. The diets were: (1) high oleic acid (16.7 energy percent oleic); (2) moderate trans (3.8 energy percent trans fatty acids); (3) high trans (6.6 energy percent trans fatty acids); and saturated (16.2 energy percent lauric + myristic + palmitic acids). There were no significant diet effects on red cell ghost fluidity determined by fluorescence polarization of the hydrocarbon probe 1,6-diphenyl-1,3,5-hexatriene (DPH) and the polar analog trimethylammonium-DPH (TMA-DPH). There were limited diet effects on fluidity of membranes as determined with DPH-propionic acid (DPH-PA) for the men. Insulin binding was more closely associated with anisotropy of fluorescence of the surface probe, DPH-PA, than with that of the other probes, which is compatible with the localization of the insulin receptor in a domain at the cell membrane surface.